Digital Currency as An Electronic Payment Method: A Legal Approach - Abed, Raghad Fawzi (International Journal of Psychosocial Rehabilitation, 2020)
The digital currency has made a qualitative impact as a means of economic exchange, and its circulation has expanded daily, without taking legal cover, as most of the countries of the world have not yet authorized dealing with it. Even those that I authorized did not regulate it or have a legal rule that allows it to be dealt with as an official currency, where it is misled to take it with confidentiality and is considered a symbol of non-transparent financial transactions, Like its use in money laundering and tax evasion crimes, and despite the seriousness of this currency, its realistic existence necessitates its legal approval and regulation and issuance by a central authority that supervises it. Especially since the text of Article 39 of the Law of the Central Bank of Iraq No. 56 of 2004 allows it to approve payment systems commensurate with the international economic development.